2014
DOI: 10.1103/physrevlett.113.047601
|View full text |Cite
|
Sign up to set email alerts
|

Superradiant Decay of Cyclotron Resonance of Two-Dimensional Electron Gases

Abstract: We report on the observation of collective radiative decay, or superradiance, of cyclotron resonance (CR) in high-mobility two-dimensional electron gases in GaAs quantum wells using time-domain terahertz magnetospectroscopy. The decay rate of coherent CR oscillations increases linearly with the electron density in a wide range, which is a hallmark of superradiant damping. Our fully quantum mechanical theory provides a universal formula for the decay rate, which reproduces our experimental data without any adju… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 32 publications
2
96
0
1
Order By: Relevance
“…A value of g/ω 0 = 0.12 was obtained with just a single QW with a moderate n e . Finally, the previously identified superradiant decay of CR in highmobility 2DEGs [27] was significantly suppressed by the presence of the high-Q THz cavity. As a result, we observed ultranarrow polariton lines, yielding an intrinsic CR linewidth as small as 5.6 GHz (or a CR decay time of 57 ps) at 2 K.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…A value of g/ω 0 = 0.12 was obtained with just a single QW with a moderate n e . Finally, the previously identified superradiant decay of CR in highmobility 2DEGs [27] was significantly suppressed by the presence of the high-Q THz cavity. As a result, we observed ultranarrow polariton lines, yielding an intrinsic CR linewidth as small as 5.6 GHz (or a CR decay time of 57 ps) at 2 K.…”
mentioning
confidence: 87%
“…It has previously been shown that the decay of CR in free space is dominated by collective radiative decay, or superradiance, in ultrahigh-mobility 2DEGs, showing a decay rate that is proportional to n e [27]. This radiative decay mechanism is very strong and dominant at low temperatures, faster than any other phase breaking scattering processes; thus, CR lines are much broader than expected from the sample mobility.…”
mentioning
confidence: 90%
“…Our first THz magneto-optical measurements were performed on the 2DEG sample, for comparison to previous studies [20][21][22][23][24][25] With the applied field, B, perpendicular to the sample (in the z direction) and the incident THz polarization in the x-direction (see the supplementary material), the electrons undergo cyclotron motion around B, which is reflected in the Faraday rotation induced in the polarization of the transmitted THz pulse. This cyclotron motion (Faraday rotation) is an odd function of B, meaning that the direction of motion reverses when B is reversed.…”
Section: Indiamentioning
confidence: 99%
“…Terahertz time-domain spectroscopy (THz-TDS) is an attractive alternative for studying the properties of low-dimensional quantum nanostructures, as THz radiation (frequency range ~0.1-10 THz) has been shown to directly probe low energy excitations, such as phonons, excitons, and Cooper pairs [19]. More recently, THz-TDS has also been used to study the cyclotron frequency and the QHE in 2DEGs (composed of e.g., doped GaAs quantum wells [20][21][22][23][24][25] and graphene [26,27]), since the THz photon energy is on the order of in these systems. However, to the best of our knowledge, there have been no THz studies on 2DHG reported to date.…”
Section: Indiamentioning
confidence: 99%
See 1 more Smart Citation